Seeing red: Traffic controls and the economy - Martin Cassini; Richard Wellings (Institute of Economic Affairs (IEA), 2016)
Not only is a high proportion of traffic regulation detrimental to road safety, the economy, and the environment, but it also imposes huge costs on road-users, taxpayers, and communities. Traffic regulation is often introduced without analysing the full cost to road-users. From 2000 to 2014, when there was little growth in traffic volumes, the number of traffic lights on Britain's roads increased by some 25%. The number of junctions controlled by signals has risen to about 15,000 with a further 18,000 pedestrian crossings. The number of instructional traffic signs in England reached 4.57 million in 2013 - an increase of 112% since 1993. The importance of the road network means the cumulative effect of such measures imposes an enormous burden on the UK economy. Just a two-minute delay to every car trip equates to a loss of approximately 16 billion a year. There is a strong economic case for replacing standard traffic regulation with strategies that harness voluntary cooperation among road-users. "Shared space" schemes - such as the one in Poynton in Cheshire - show the transformational benefits of this unregulated, design approach. A high proportion of traffic lights should be replaced by filter-in-turn or all-way give-ways. Many bus lanes, cycle lanes, speed cameras and parking restrictions should also go. Culling such traffic management infrastructure would deliver substantial economic and social benefits.
Keywords: R48; R42; R41; R49; D61; R48; R42; R41; R49; D61; 330